2017
DOI: 10.3389/fnmol.2017.00129
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Ketosis Affects Metabolism and Behavior in Sprague-Dawley Rats in Both Control and Chronic Stress Environments

Abstract: Nutritional ketosis may enhance cerebral energy metabolism and has received increased interest as a way to improve or preserve performance and resilience. Most studies to date have focused on metabolic or neurological disorders while anecdotal evidence suggests that ketosis may enhance performance in the absence of underlying dysfunction. Moreover, decreased availability of glucose in the brain following stressful events is associated with impaired cognition, suggesting the need for more efficient energy sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 80 publications
3
45
1
Order By: Relevance
“…Lactate/pyruvate ratio (27 [17-44] vs. 27 vs. 28 ), brain tissue PO 2 (29 [19-39] vs. 29.5 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] vs. 29 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] mm Hg) and ICP (10 [3-20] vs. 11 [5][6][7][8][9][10][11][12][13][14][15][16][17] (Figure 3(a)), representing a median 4.7-fold decrease of blood KB from fasting to stable nutrition state. Median individual plasma/brain KB ratio was 11.…”
Section: Modulation Of Cerebral Ketone Metabolism By Nutritional Statementioning
confidence: 99%
See 1 more Smart Citation
“…Lactate/pyruvate ratio (27 [17-44] vs. 27 vs. 28 ), brain tissue PO 2 (29 [19-39] vs. 29.5 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] vs. 29 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] mm Hg) and ICP (10 [3-20] vs. 11 [5][6][7][8][9][10][11][12][13][14][15][16][17] (Figure 3(a)), representing a median 4.7-fold decrease of blood KB from fasting to stable nutrition state. Median individual plasma/brain KB ratio was 11.…”
Section: Modulation Of Cerebral Ketone Metabolism By Nutritional Statementioning
confidence: 99%
“…15,16 Increasing KB metabolism through fasting or diet-induced ketosis promotes brain resistance to stress and injury 2 and attenuates acute cerebral damage. [16][17][18] Ketone body supplementation, e.g. with the use of medium-chain triglycerides (MCTs) ketogenic diets, has therefore emerged as a potential non-pharmacological neuroprotective therapy.…”
Section: Introductionmentioning
confidence: 99%
“…; Brownlow et al . ; Leckey et al . ), but ketone esters allow blood ketones to reach ∼3‐fold higher levels than salts, with less incidence of gastrointestinal problems (Stubbs et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, exogenous ketone supplements recently emerged as a novel approach to induce ketosis. Exogenous supplements are available either in the form of ketone salts or ketone esters (Cox et al 2016;Brownlow et al 2017;Leckey et al 2017), but ketone esters allow blood ketones to reach ß3-fold higher levels than salts, with less incidence of gastrointestinal problems (Stubbs et al 2017;Sansone et al 2018). Recent studies in our and other laboratories have shown that post-exercise ingestion of the ketone monoester (R)-3-hydroxybutyl (R)-3-hydroxybutyrate (KE) stimulates markers of protein synthesis and potentially also muscle glycogen repletion following exercise (Holdsworth et al 2017;Vandoorne et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…KD treatment is a relatively safe treatment method, which can play a role in cognitive and motor function of children, and a large number of tests have confirmed that KD can control the onset of pharmacoresistant epileptic encephalopathy and improve cognition, which may be reflect a reduction in memory impairment caused by seizures in KD‐treated children (Jiang et al., ). The mechanism underlying KD treatment may be related to neuroprotection (Hallböök, Ji, Maudsley, & Martin, ), a reduction in clinical seizure activity, improved energy metabolism, and a reduction in stress‐induced biochemical effects within the hippocampus, thus improving the internal environment and improving cognitive and behavioral function (Brownlow, Jung, Moore, Bechmann, & Jankord, ).…”
Section: Discussionmentioning
confidence: 99%